Adults-only hotel – a potential specialization for success? - Mondok Anita; Szüle Picabo Heder („RIK-U” Kft., 2020)
Abstract. Maintaining a healthy family includes the mental and psychological health of parents. Children are a constant part of parents’ lives, but the leisure time spent by parents to themselves returns in a more patient behaviour of them in childcare. The basic concept of adults only hotels is to create a relaxed, child-free environment for parents or childless guests. The article presents the results of a questionnaire-based survey exploring the popularity and acceptance of adults only hotels in a sample of 444 respondents.
https://kmf.uz.ua/wp-content/uploads/2020/09/final_2_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008123
Keywords: adults only hotel; service; Hungary